The Molecular Basis of Human Cancer - Coleman, William B.; Tsongalis, Gregory J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2017)
This book covers the concepts of molecular medicine and personalized medicine. Subsequent chapters cover the topics of genomics, transcriptomics, epigenomics, and proteomics, as the tools of molecular pathology and foundations of molecular medicine. These chapters are followed by a series of chapters that provide overviews of molecular medicine as applied broadly to neoplastic, genetic, and infectious diseases, as well as a chapter on molecular diagnostics. The volume concludes with a chapter that delves into the promise of molecular medicine in the personalized treatment of patients with complex diseases, along with a discussion of the challenges and obstacles to personalized patient care. The Molecular Basis of Human Cancer, Second Edition, is a valuable resource for oncologists, researchers, and all medical professionals who work with cancer.
Cancer Epidemiology: Incidence and Etiology of Human Neoplasms -- Essential Concepts and Techniques in Molecular Biology -- Cancer Genomics -- Cancer Cytogenetics -- The Epigenetic Basis of Human Cancer -- Cancer Proteomics -- An Overview of Cancer Genes -- Oncogenes and the Initiation and Maintenance of Tumorigenesis -- Positive Mediators of Cell Proliferation in Neoplasia: Growth Factors and Receptors -- Senescence, Apoptosis, and Cancer -- Novel Cancer Therapies Targeting Angiogenesis -- Beyond the Primary Tumor: Progression, Invasion, and Metastasis -- Simple Sequence Mutations -- Single Nucleotide Polymorphisms and Cancer Susceptibility -- Chromosomes and Chromosomal Instability in Human Cancer -- Epigenetic Mechanisms in Cancer Development -- MicroRNAs and Cancer -- Erionite and Asbestos in the Pathogenesis of Human Malignant Mesotheliomas -- Viral Mechanisms in Human Carcinogenesis -- Hormonal Carcinogenesis: The Role of Estrogens -- Sporadic Cancers -- Hereditary Cancer -- Retinoblastoma: Clinical and Molecular Perspectives -- Xeroderma Pigmentosum and the DNA Damage Response to Ultraviolet Light -- Hereditary Colorectal Cancer -- Hereditary Breast and Ovarian Cancer -- The Molecular Basis of Prostate Carcinogenesis -- Molecular Basis of Lung Carcinogenesis -- The Molecular Basis of Skin Carcinogenesis -- The Molecular Biology of Leukemias -- Molecular Mechanisms in Non-Hodgkin Lymphoma -- The Molecular Pathology of Head and Neck Squamous Cell Carcinoma -- Ovarian Cancer -- Molecular Pathology of Bone and Soft Tissue Tumors -- The Molecular Biology of Human Brain Tumors -- Cancer Drug Discovery and Anticancer Drug Development -- Biological Principles and Clinical Application of EGFR Inhibitors in Cancer -- Targeting Oncoproteins for Molecular Cancer Therapy -- Therapeutic Agents that Inhibit Angiogenesis -- Small Molecule Inhibitors -- Molecular Detection and Diagnosis of Cancer -- Gene Therapy in the Treatment of Human Cancer -- Personalized Medicine for the Treatment of Human Cancer.
Keywords: Medicine; Oncology; Medicine & Public Health; Oncology